Teacher's aides in kindergarten: Effects on achievement for students with disabilities. Issue 5 (3rd September 2018) - Gottfried, Michael A.
ABSTRACT: Over the past 20 years, the number of teacher's aides in the United States has more than doubled, potentially in response to the growth of special education programs now taking place in general education schools. Surprisingly, little research at all has focused on the role that teacher's aides may play in improving student achievement, and no known study had examined this for students with disabilities. The author addressed this void by examining how teacher's aides link to achievement outcomes for students with disabilities in kindergarten. Using nationally representative data, the findings suggest that students with disabilities in full-day kindergarten have higher reading and mathematics outcomes at the end of kindergarten when the classroom has a teacher's aide. In contrast, there was no observed benefit for students with disabilities in part-day kindergarten. The size and strength of this relationship differs by individual characteristics and teacher and classroom characteristics. Implications are discussed.